Perancangan Pondok Pesantren Modern di Kota Tangerang dengan Konsep Asitektur Islam - Firdaus, Alwi; Subagya, Karya; Suryandari, Putri (MAESTRO, 2020)
Education is an important part of life that also distinguishes humans from other livng things. Education is a systematic conscious effort in developing all the potential that exists in humans to become fully human. Indonesian citizens are citizens who have a religious life, so that to meet the needs of adequate education, every citizen wants to be met the need for religious education and education in general. The application of islamic architecture because of the similarities in the effort to restore and carry out islamic values in various aspects. The application of islamic architecture in pesantren buildings is more to the physical building which is expected to be able to produce a building as well as a place to gain knowledge in which islamic values can be applied.